Platymya fimbriata - DRABER-MOŃKO, Agnieszka (Zenodo, 2015)
Platymya fimbriata (Meigen, 1824) Tachina fimbriata Meigen, 1824: 337. Type locality: not given (probably Germany, Stolberg). Distribution: Palaearctic: Europa (all), Transcaucasia, C. Asia, M. East, Mongolia, Russia (W. Russia, S. Siberia, the Russian Far East: Kamchatka, Primorsk Territory, Sakhalin, S. Kuril Islands (Iturup, Kunashir, Shikotan)) (Richter 2004), Korea (Chao et Xue 1998), China Provinces (Chongqing M., Heilongjiang, Sichuan, Shanxi, Tibet); Oriental: China Provinces (Guizhou, Yunnan) (O’Hara, Shima & Zhang 2009). : Published as part of DRABER-MOŃKO, Agnieszka, 2015, State of knowledge of the tachinid fauna of Eastern Asia, with new data from North Korea. Part V. Exoristinae, pp. 79-98 in Fragmenta Faunistica 58 (2) on page 94, DOI: 10.3161/00159301FF2015.58.2.079, http://zenodo.org/record/6251824 : {"references": ["Richter V. A. 2004. Fam. Tachinidae - tachinids. In: Sidorenko V. S. (ed.), Key to the insects of Russian Far East. Vol. VI. Diptera and Siphonaptera. Part 3 pp. 148 - 398. Vladivostk, Dal'nauka. 657 pp. [In Russian].", "O'HARA J. E., SHIMA H. & ZHANG C. T. 2009. Annotated Catalogue of the Tachinidae (Insecta: Diptera) of China. Zootaxa 2190: 1 - 236."]}